KEEFEKTIFAN STRATEGI ASOSIASI KOTAK KATA DALAM MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN PESERTA DIDIK DALAM MENGHAFAL ASMAUL HUSNA - Moh Imron; Lukman Hakim Hakim AI (Nurul Jadid University, 2018)
This research is an experimental research using pre-test post-test control group design. The subjects consisted of 56 high school grade X High School students selected using purposive sampling technique. Then 56 female students were placed into the control group and experimental group with the provisions of Class X Language 3 as a control group, while X Language 2 as the experimental class. Data collection was done by using test and non test. To ensure that the instrument has the validity and reliability that qualify, then conducted factor analysis and reliability test. Data analysis technique used for hypothesis is t-test technique. The results of this study indicate that the Word Box Association Method effectively increases learning motivation and the ability to memorize students. The average score of learning motivation and the ability to memorize at the time of posttest between the control group and the experimental group differed significantly. The mean score of learning motivation and memorization ability of the experimental group is higher than the control group's average score.